Perceptions and Experiences of Medical Assistance in Dying Among Illicit Substance Users and People Living in Poverty. (November 2021) - Shaw, Jessica; Harper, Laura; Preston, Emma; Wright, Alysia; Kelly, Michaela; Wiebe, Ellen
Since medical assistance in dying (MAiD) became legal in Canada in 2016, there have been concerns about vulnerable people feeling pressured to end their lives. It is important to understand what people in marginalized communities know and feel about MAiD in order to help prevent any pressure to hasten death and to prevent any barriers to accessing assisted death. This qualitative study explored the perceptions and experiences of MAiD and other end-of-life care options with 46 people who were illicit substance users, living in poverty, or who worked with marginalized people in these communities. Six broad themes were identified: the importance of family, friends, and community; the effects of the opioid crisis; barriers to accessing end-of-life care services; support for MAiD; the difference between suicide and MAiD; and what constitutes a good death. Findings from this research may be used to help inform future legislation, professional guidelines, and standards of best practice.